2009
DOI: 10.1088/0004-637x/691/2/1109
|View full text |Cite
|
Sign up to set email alerts
|

ON THE DYNAMICAL EVOLUTION OF H II REGIONS: AN INVESTIGATION OF THE IONIZED COMPONENT OF W4, A GALACTIC CHIMNEY CANDIDATE. I. KINEMATICS AND DYNAMICS IN THE LATITUDE RANGE 0° ⩽b⩽ 3°

Abstract: In the second of this two-paper series, we present results associated with an Hα investigation, obtained using the Fabry-Perot interferometer FaNTOmM, of the tenuous ionized material found embedded in the northern portion of W4. W4 is a promising candidate for a galactic chimney, likely connected with the galactic corona, and presents evidence of shell fragmentation. We present the quantitative method for identifying shell breakout that allows us to characterize the giant H i supershell/H ii region W4 as enclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 60 publications
(70 reference statements)
0
29
0
Order By: Relevance
“…W4 also exhibits a 1 • loop of emission to the south of IC 1805 (Lagrois & Joncas 2009a), where the bubble created by IC 1805's predecessors is encountering denser material in the Galactic Plane. IR and radio work (Terebey et al 2003) has shown that the W4 shell is very inhomogeneous, allowing 40% of the MYSC's ionizing photons to leak out of the superbubble and ionize the surrounding ISM.…”
Section: W4mentioning
confidence: 99%
“…W4 also exhibits a 1 • loop of emission to the south of IC 1805 (Lagrois & Joncas 2009a), where the bubble created by IC 1805's predecessors is encountering denser material in the Galactic Plane. IR and radio work (Terebey et al 2003) has shown that the W4 shell is very inhomogeneous, allowing 40% of the MYSC's ionizing photons to leak out of the superbubble and ionize the surrounding ISM.…”
Section: W4mentioning
confidence: 99%
“…In order to extract purely kinematic broadening effects from the observed Hα linewidths, the standard method of quadratic subtraction presented in e.g. Lagrois & Joncas (2009a) was used (see ). The broadening excess caused by thermal motions was subtracted by estimating the electron temperature for each targeted nebula.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…These filaments most likely trace out the spatial disposition, on the plane of the sky, of the eroded (sometimes fully ionized) molecular envelopes. The central structure is surrounded by diffuse ionized material likely associated with photoevaporated flows kinematically in agreement with the Champagne phase (Lagrois & Joncas 2009a). One of these flows (displaying blue shades in Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Lagrois & Joncas (2009a,b) provide a high spectral‐resolution (<15 km s −1 ) kinematical investigation of the H + content on an appreciable fraction of the IC 1805 ionized extent. The northernmost portions (63°20′ ≤ δ 2000 ≤ 66°50′) of the large ovoid bubble have shown kinematical evidence for high‐latitude gas venting and the early development of a Galactic chimney.…”
Section: The Ic 1805 Gas Complexmentioning
confidence: 99%
See 1 more Smart Citation